Physical properties of Fe doped In2O3 magnetic semiconductor annealed in hydrogen at different temperature - Hussein Baqiah, Hussein Abdullah; Ibrahim, Noor Baa'yah; Shaari, Abdul Halim; Chen, Soo Kien; Lim, Kean Pah; Awang Kechik, Mohd Mustafa (Elsevier, 2016)
The effects of hydrogen-annealing at different temperatures (300, 400, 500 and 600°C) on physical properties of In2−xFexO3 (x=0.025) thin film were investigated. The structural measurement using XRD shows that the film has a single In2O3 phase structure when annealed in hydrogen at 300–500°C, however when annealed in hydrogen at 600°C the film has a mixed phase structure of In2O3 and In phases. The electrical measurements show that the carrier concentrations of the films decrease with the increase of hydrogen-annealing temperature in the range 300–500°C. The optical band gap of the films decreases with increasing hydrogen-annealing temperatures. The saturation magnetisation, Ms, and coercivity of films increase with the increment of hydrogen annealing temperature. The film annealed at 300°C has the lowest resistivity, ρ=0.03 Ω cm, and the highest carrier concentrations, n=6.8×1019 cm−3, while film annealed at 500°C has both good electrical (ρ=0.05 Ω.cm and n=2.2×1019 cm−3) and magnetic properties, Ms=21 emu/cm-3.